Model-driven Structural and Statistical Testing of Robot Cooperation and Reconfiguration - Saglietti, Francesca; Meitner, Matthias (Proceedings Third Workshop on Model-Driven Robot Software Engineering, 2016)
This article proposes a model-based approach to structural and statistical testing of cooperating and reconfigurable autonomous robots. Based on Coloured Petri Net models of cooperative behaviour, it summarizes the main results achieved in the context of two European ARTEMIS projects. As an example, a CPN model of autonomous and reconfigurable trolleys moving within a common environment is considered. The results allow for both a qualitative and a quantitative reliability analysis. <br